A 3D Approach for THD Lubrication in Tilting Pad Journal Bearing—Theory and Experiment. Issue 1 (2nd January 2020) - Bizarre, L.; Andersen, T. B.; Daniel, G. B.; Santos, I. F.; Cavalca, K. L.
Abstract: The study of rotating machines stands out in the context of systems and structures due to the significant number of typical phenomena that may be present during the operation of such equipment. Rotating systems play an important role in industrial environments, with a wide range of application, namely, pumps, turbines, generators and compressors, and turbochargers, among others. Given this context, tilting pad journal bearings (TPJBs) can offer considerable stability to the rotor system due to its damping and stiffness characteristics, especially under high rotation speeds, whereas journal bearings with a fixed geometry may be subjected to fluid-induced instability. Consequently, thermal effects are significant in rotating machines to evaluate the behavior of hydrodynamic bearings due to the increase in shear effects in the lubricant caused by the rotation speed, leading to excessive temperature increase under specific operational conditions and, therefore, significant changes in lubricant viscosity. These effects may influence the dynamic characteristics of bearings, affecting the dynamic response of the entire system. From this perspective, a specific test rig was designed to perform the characteristic uncoupled motion of the shaft when supported by this kind of bearing. Experimental tests were directly compared with numerical models, showing promising results. In addition, the thermohydrodynamic (THD) lubrication was numerically solved by a finite volume method, considering an approach for a 3D THD model and the pivot flexibility.